2015
DOI: 10.1007/s40881-015-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Online field experiments: a selective survey of methods

Abstract: The Internet presents today's researchers with unprecedented opportunities to conduct field experiments. Using examples from Economics and Computer Science, we present an analysis of the design choices, with particular attention to the underlying technologies, in conducting online field experiments and report on lessons learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…For example, lenders who join teams might simply be those who are more active in general (4). To establish the causal relationship between group membership and prosocial lending, we use a randomized field experiment that enables us to combine the control of a laboratory experiment with the external validity of a field study (6,7).…”
mentioning
confidence: 99%
“…For example, lenders who join teams might simply be those who are more active in general (4). To establish the causal relationship between group membership and prosocial lending, we use a randomized field experiment that enables us to combine the control of a laboratory experiment with the external validity of a field study (6,7).…”
mentioning
confidence: 99%
“…Internet technologies have opened new frontiers in social collective action and knowledge and the gathering of scientific data in the forms of online crowdsourcing and digital field experiments (see [153][154][155][156][157] for reviews). Crowdsourcing can be understood as the leveraging of information technologies for individual participation in collective processes [158], such as crowdfunding, mapping applications such as Waze, and citizen science data collection efforts (e.g., Christmas Bird Count [159] and Geo-Wiki [160]).…”
Section: Online Crowdsourcing and Field Experimentsmentioning
confidence: 99%
“…Recent work investigating the ethical practices of CSCW researchers found that 22% of researchers surveyed held the view that obtaining informed consent is always necessary [37]. At the same time, waivers of informed consent are sought and obtained in field experiments across the social sciences [23,9]. However, the omission of informed consent was one of the key controversial issues discussed in the turmoil surrounding Facebook's emotional contagion experiment.…”
Section: Informed Consentmentioning
confidence: 99%